PROTEKSI PETIR PADA TRANSISI SALURAN UDARA DAN BAWAH TANAH TEGANGAN MENENGAH 20 kV - Irianto, Chaerul Gagarin; Abduh, Syamsir (Jurnal Teknik Elektro, 2003)
This paper summarizes the main results of a study aimed at determining the maximumlightning overvoltages in branchless underground feeder protected by metal-oxide arresters.The study has two parts. Initially, it is performed assuming an ideal behavior of allcomponents: the goal is to gain insight into the physical phenomenon. This will be useful tounderstand the main results obtained in the second part, where an advanced model is usedfor representing arresters.Keywords: Lightning, Surge Arresters, Underground Cables